Data for: Identity in Court Decision-Making - Ahrsjö, Ulrika; Niknami, Susan; Palme, Mårten (Stockholm University, 2023)
The data set "ANP_lay_judge_data" consists of compiled information from protocols pertaining to 15,456 criminal court hearings; all criminal court trials in Stockholms Tingsrätt (the Stockholm district court) in years 2000 to 2004. Information was collected from the Stockholm court archive by photocopying the trial and sentencing protocols, and compiled into a data set holding information about the defendant, judge, lay judges and the prosecutor, as well as criminal charges, sentencing outcomes and additional trial information. Note that all individual identifiers are pseudonymized. Access to the data set (in .dta or .csv format) is subject to application, this folder contains a detailed description of it and a variable list.

The data set was created for a research project on the effect of judge and other judicial decision-makers' background, in terms of demographics and socioeconomic conditions, on court sentencing outcomes. Its first research paper investigates whether similarities between the defendant and the jurors result in milder sentences, i.e. identity effects.

Datan "ANP_lay_judge_data" består av en sammanställning av dokument från 15,456 domar gällande brottsmål i Stockholms Tingsrätt mellan åren 2000 och 2004. Dessa är insamlade från protokoll och domar lagrade i Tingsrättens arkiv, och rör alla brottsmål som avgjordes de aktuella åren. Dokumenten är fotograferade och sedan sammanställda till ett data set är varje observation är en person och brottsmål. Datan innehåller information om den tilltalade, domaren, nämndemännen och åklagaren i varje mål, utöver åtalspunkter och påföljder samt ytterligare information om rättegången. Alla variabler som rör personuppgifter är pseudonymiserade. Utlämning av datan (som .dta eller .csv) görs mot prövning, här tillhandahålls en utförlig beskrivning av metod samt en variabellista.

Datan är framtagen för ett forskningsprojekt om effekten av domares och andra juridiska beslutsfattares demografisks och socioekonomisks backgrund på domstolsutfall. Projektets första del undersöker huruvida likheter mellan tilltalade och nämndemän leder till mildare rättsutfall, s.k. identitetseffekter.
Data för: Identity in Court Decision-Making
Keywords: POLITICAL REPRESENTATION; POLITISK REPRESENTATION; CRIMINAL JUSTICE SYSTEM; RÄTTSVÄSENDE; DELINQUENCY; BROTTSLIGHET; JURIES; NÄMNDER (DOMSTOL); LAW AND JUSTICE; LAG OCH RÄTT; Crime and law enforcement; Kriminalitet och rättstillämpning; Economics; Nationalekonomi